2008
DOI: 10.1007/s10265-007-0143-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultraviolet-B irradiation on the cuticular wax of cucumber (Cucumis sativus) cotyledons

Abstract: Cucumber seedlings were grown under three doses of supplemental ultraviolet-B (UV-B) irradiation to examine the effects on the surface structure of the cotyledons. Medium and high doses of irradiation induced glazing (formation of translucent, glossy layers) on the adaxial surfaces of cotyledons, especially those exposed to a high dose of UV-B. Observation with a scanning electron microscope revealed that the adaxial surfaces of cotyledons exposed to a medium dose of UV-B and controls became rough in appearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 26 publications
3
17
1
1
Order By: Relevance
“…Steinmuller and Tevini [64] reported that enhanced UV-B radiation increased wax content by 23% in barley and 28% in bean. Fukuda et al [65] observed an increase in the amount of cuticular wax per unit leaf area by two fold as a result of UV-B radiation in cucumber, suggesting that UV-B acts on the cuticular biosynthetic pathway. Our results strongly suggest that C. citratus plants also protect themselves against UV-B irradiation by developing this stress avoidance mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…Steinmuller and Tevini [64] reported that enhanced UV-B radiation increased wax content by 23% in barley and 28% in bean. Fukuda et al [65] observed an increase in the amount of cuticular wax per unit leaf area by two fold as a result of UV-B radiation in cucumber, suggesting that UV-B acts on the cuticular biosynthetic pathway. Our results strongly suggest that C. citratus plants also protect themselves against UV-B irradiation by developing this stress avoidance mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, one of the most important functions for cuticular wax is to protect plants from excessive ultraviolet (UV) light. Many studies showed that elevated UV-B radiation affects plant cuticular wax formation and gas exchange (Jansen et al, 1998; Fukuda et al, 2008; Jiang et al, 2009). It was found that cuticular wax content increases by 20–28% in cucumber ( Cucumis sativus L.), bean ( Phaseolus vulgaris L.), and barley ( Hordeum vulgare L.) when plants are exposed to UV-B light (Steinmüller and Tevini, 1985).…”
Section: Linking Cuticular Wax To Plant Drought Tolerancementioning
confidence: 99%
“…The cuticular waxes can further help in protecting plants from high light stress [101]. The cuticular wax has a role in protecting plants from excessive ultraviolet (UV) light and there are reports indicating that elevated UV-B radiation can affect plant cuticular wax formation [101,159,160]. Based on the existing information, as mentioned above, cuticular wax, can be treated as the first protective layer and an important trait contributing for both biotic and abiotic stresses.…”
Section: Abiotic Stressesmentioning
confidence: 99%